The mindfulness edge : - Tenney, Matt (John Wiley and Sons, 2016)
The one habit that can improve almost every leadership skill There is a simple practice that can improve nearly every component of leadership excellence and it doesn't require adding anything to your busy schedule. In The Mindfulness Edge, you'll discover how a subtle inner shift, called mindfulness, can transform things that you already do every day into opportunities to become a better leader. Author Matt Tenney has trained leaders around the world in the practice of mindfulness. In this book, he partners with neuroscientist Tim Gard, PhD, to offer step-by-step, practical guidance for quickly and seamlessly integrating mindfulness training into your daily life--rewiring your brain in ways that improve both the 'hard' and 'soft' skills of leadership.